1999
DOI: 10.1159/000016507
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acidified Fluoride Gel on Abrasion Resistance of Eroded Enamel

Abstract: The objective of the study was to evaluate the abrasion resistance of eroded enamel brushed with an acidified fluoride gel. Each enamel specimen was prepared from one of 64 bovine incisors. The specimens were embedded in acrylic resin, ground flat, polished and subsequently covered with a tape exposing an area of 1.8×10.0 mm in the center of the enamel specimens. The samples were alternatingly stored in a demineralizing solution (5 min) and a remineralizing solution (1min) four times. An acidic soft drink (Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
18

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 11 publications
9
68
0
18
Order By: Relevance
“…3 Given that there has been an increase in the prevalence of erosive tooth wear (referring to tooth wear by erosion combined with mechanical factors, such as attrition and toothbrush abrasion), and an increase in the longevity of teeth in recent decades, clinical management should focus on early detection and prevention before a restorative approach is considered. 4 Previous reports have indicated that topical fluoride can protect enamel and dentine against erosion 5,6 and a combination of erosion and toothbrush abrasion, [7][8][9] but not against attritional wear between opposing enamel and dentine specimens. 10 Recently, Tooth Mousse (GC Corporation, Japan) whose principal ingredient is an anticariogenic remineralizing agent CPP-ACP (casein phosphopeptide-amorphous calcium phosphate nanocomplexes) has been recommended for the management of dental erosion.…”
Section: Introductionmentioning
confidence: 99%
“…3 Given that there has been an increase in the prevalence of erosive tooth wear (referring to tooth wear by erosion combined with mechanical factors, such as attrition and toothbrush abrasion), and an increase in the longevity of teeth in recent decades, clinical management should focus on early detection and prevention before a restorative approach is considered. 4 Previous reports have indicated that topical fluoride can protect enamel and dentine against erosion 5,6 and a combination of erosion and toothbrush abrasion, [7][8][9] but not against attritional wear between opposing enamel and dentine specimens. 10 Recently, Tooth Mousse (GC Corporation, Japan) whose principal ingredient is an anticariogenic remineralizing agent CPP-ACP (casein phosphopeptide-amorphous calcium phosphate nanocomplexes) has been recommended for the management of dental erosion.…”
Section: Introductionmentioning
confidence: 99%
“…4 The influence of topical fluoride on the degree of abrasion of acid eroded enamel has been investigated. 5,6 Enamel blocks cycled between 5 min acid immersion and linear tooth brushing resulted in significantly less wear with the fluoride toothpaste compared with an otherwise identical non-fluoride formulation. 5 Brushing eroded bovine enamel with acidulated fluoride gels with a pH of 4.5 and 7.0 were compared with unfluoridated gels with the same pHs.…”
Section: Introductionmentioning
confidence: 99%
“…Attin et al (Attin et al, 1999) reported that, fluoridation was effective in increasing resistance of enamel against demineralization by erosive substances. Similarly, the findings of this present study demonstrated that the resistance of enamel against the erosive demineralization caused by 38% HP application was increased after 1% TiF 4 treatment.…”
Section: Effects Of Topical Fluoride Agents On Enamel Surface In Coopmentioning
confidence: 99%